Wildlife Values Dilemmas: Where Do You Stand? - Knapp, Clifford (Wildlife Rehabilitation Bulletin, 2016)
This manuscript consists of a brief introduction to values education, including the definitions of key terms, the purpose of the symposium presentation, and guidelines for maximizing the benefits of the session. The body of the paper consists of selected valuing strategies designed to promote awareness and discussion of various wildlife dilemmas. Some of these dilemmas were presented during a general session of the National Wildlife Rehabilitators Association symposium at the Marriott Hotel in Schaumburg, IL on 20 February 1991. Examples of several general types of values strategies are values voting, rank order, trio/quartet sharing, values continuum, and other questioning approaches to wildlife values dilemmas.